Studi Literatur : Pengaruh Penerapan Teknik Akupresur Terhadap Penurunan Intensitas Nyeri Persalinan Kala I - Nur Mufidah Alfi; Indah Ayu Nur Hasanah; Agriyaningsih Oktaviana Hadi (Jurnal Medicare, 2025)
Background: Labor pain is a physiological condition that occurs in almost all women giving birth. Controlling labor pain is kind of a basic goal during labor. There are many pharmacological and non-pharmacological methods used to control pain and help mothers to cope with pain. Acupressure technique is a non-pharmacological method that is easy and has no side effects that can be used as an alternative to reduce pain during the labor. Objective: To determine the effect of applying acupressure techniques on reducing the intensity of labor pain during the 1st stage. Methods: This study used the Literature Review method with three databases, namely Pubmed NCBI, Research Gate and Google Scholar which were published in the last 5 years. Result: 6 articles that were reviewed met the inclusion criteria used in the study. All of them stated that there was an effect of giving acupressure techniques on reducing the intensity of labor pain during the 1st stage. The research design used was 3 articles of Quasy-Experiment, 1 article of Pre-Experiment and 2 articles of Randomized Controlled Trial (RCT). Conclusion: Acupressure is effective in reducing the intensity of first stage labor pain.